Participatory ecological restoration and cultural ecosystem services: a necessary relationship - González-Molina, Hilda Zolangie; Trilleras , Jenny M.; Pyszczek , Oscar Luis; Romero-Duque, Luz Piedad (Instituto de Ecología, A.C., 2022)
Background and Aims: Inclusion of cultural ecosystem services in participatory ecological restoration projects is scarce, despite being recognized as important. The objective of this study was to analyse the role of cultural ecosystem services associated with participatory ecological restoration processes in the Ecoparque Sabana, municipality of Tocancipá, Colombia, by assessing the perceptions and social representations of the stakeholders of the process. Methods: A semi-structured interview was applied to administrators, workers and visitors of the Ecopark, as well as inhabitants of the municipality Tocancipá, to assess the perceptions and social representations of the stakeholders of the process. Ecosystem services evaluated were scenic beauty, spiritual and artistic inspiration, sense of place, social relationships, ecotourism, educational value and cultural heritage. The information was analysed using text mining, discourse analysis, and multiple correspondence analysis. Key results: Cultural ecosystem services play a key role within the participatory ecological restoration process. Participatory ecological restoration processes generated a positive perception in the majority of the interviewees (91%). Moreover, differences were found in the perceptions of services according to the group of actors to which they belong, gender and place of residence (rural/urban). The increase in the number of visits resulted in an increase in the support from visitors to the restauration process. Educational values and ecotourism gave added value to restoration processes, since they promote social relations, conservation and generate deep-rooted relationships. Conclusions: Incorporating ecosystem services including cultural ones, in participatory ecological restoration processes is necessary. The importance of the cultural component was verified as the restoration progressed, evidencing the strengthening of the link between the recovery of biophysical aspects with cultural aspects in the generation of social context (tejido social).